Féeton (B − L gauge boson) dark matter testable in future direct detection experiments - Yu Cheng; Jie Sheng; Tsutomu T. Yanagida (Journal of High Energy Physics)
Abstract In this paper, we revisit the féeton (gauge boson of U(1) B−L symmetry) dark matter scenario, and first point out the U(1) gauge symmetry can be a linear combination of the B – L and the SM hypercharge gauge symmetries. With the redefinition of B – L charge of fermions, the coupling between electron and féeton can be enhanced. After showing the parameter space required from the DM stability and cosmic production, we discuss the potential for verifying them in dark matter direct detection experiments. The results show that future experiments, such as SuperCDMS, have a sensitivity to reach the féeton DM region consistent with its cosmic production.